Designing Promotional Media for Dapur Uti Pah Catering - Laksmi, Arieviana Ayu; Patria, Asidigisianti Surya; Martadi, Martadi; Kristiana, Nova; Anggalih, Nanda Nini; Carreca, Irhamna Nirbhaya (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
Dapur Uti Pah is a micro, small, and medium enterprise (MSME) operating in the food and beverage sector in Sidoarjo Regency, Indonesia. Despite offering high-quality catering services, the business faced challenges in promotional effectiveness due to outdated packaging, limited promotional media, and suboptimal use of digital platforms. The objective of this research was to design and implement integrated promotional media to strengthen Dapur Uti Pah’s promotional media, expand market reach, and enhance customer engagement. The study applied a qualitative participatory action research (PAR) design involving collaboration between researchers and the business owner. Data were collected through Focus Group Discussions (FGDs), field observations, interviews, documentation reviews, and customer surveys. The intervention consisted of developing digital media, including social media content, as well as printed media such as redesigned logos, packaging, banners, and uniforms. The results showed a significant improvement in brand visibility and customer interaction, reflected in increased social media engagement, order volume, and customer satisfaction. The study concludes that modern and consistent promotional media combined with digital marketing strategies can effectively improve MSME competitiveness and market sustainability in the catering industry.